Diseño de un sistema web para el proceso de vinculación con la sociedad de la carrera de Sistemas de Información. - Coque Sandoval, Daniela del Pilar (2020)
In our country the web systems are currently the main axis of the companies and institutions whose purpose is to offer quickly through online links from any geographical location, allowing an increase in productivity and information management. For this reason, it is considered important to develop a web Information System for the processes of Linking with the society of the Information Systems Major. The literature has allowed the identification of similar works to this computer development work, however, the proposed web system is developed according to the own characteristics that are generated in the daily work in the process of Linking with Society in the Subject in question. The methodology used for the development of the web application corresponds to the methodology SCRUM, because this methodology applied is executed regularly for the execution of good practices in software development based on procedures of flexibility and productivity, For the design of the page we used the tools Hypertext Preprocessor (PHP), Cascading Style Sheets (CSS), Programming Language (JAVA), Visual Paradigm and the IEE830 standard to specify requirements, and its connection to the database was done through the software Database Management System (MySQL). As a result, an information system is obtained that contains a friendly interface where you can find relevant information about the projects of the Link with Society planned and executed until now. It is concluded that this type of application contributes as support tools to present relevant information of the Society Relationship management that develops the Career.